2003
DOI: 10.1002/jcla.10076
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐related differences in hepatic activity of alcohol dehydrogenase isoenzymes and aldehyde dehydrogenase in humans

Abstract: Alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH), which are most abundant in the liver, are the main enzymes involved in ethanol metabolism in humans. Gender-related differences in total liver ADH and ALDH activity among different animal species have been observed in many studies. We measured total ADH and ALDH activity, and the activity of class I-IV ADH in the livers of male and female patients. Total ADH and class I and II ADH activities were significantly higher in males than in females (P=0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 22 publications
1
57
1
Order By: Relevance
“…Heavy alcohol consumption enhances the probability of both atrial and lifethreatening ventricular arrhythmias and atrioventricular block through the destabilization of potassium and magnesium metabolism and the stimulation of catecholamine. 28,29 Further, women have lower alcohol dehydrogenase activity in the liver than men, 30 so that women have higher blood alcohol concentrations than men after ingestion of the same dose of alcohol, even when the dose is adjusted for body weight. 31 The Nurse's Health study 19 did not find the excess mortality, but the number of deaths among heavy drinkers of Ն30g ethanol per day in that cohort was also small (nϭ9).…”
Section: Discussionmentioning
confidence: 99%
“…Heavy alcohol consumption enhances the probability of both atrial and lifethreatening ventricular arrhythmias and atrioventricular block through the destabilization of potassium and magnesium metabolism and the stimulation of catecholamine. 28,29 Further, women have lower alcohol dehydrogenase activity in the liver than men, 30 so that women have higher blood alcohol concentrations than men after ingestion of the same dose of alcohol, even when the dose is adjusted for body weight. 31 The Nurse's Health study 19 did not find the excess mortality, but the number of deaths among heavy drinkers of Ն30g ethanol per day in that cohort was also small (nϭ9).…”
Section: Discussionmentioning
confidence: 99%
“…We Alcohol dehydrogenase (ADH) isoenzymes and aldehyde dehydrogenase (ALDH) activity in the sera of patients with colorectal cancer hypothesised that the changed activities of these enzymes in cancer cells were reflected in the serum and perhaps could thus be helpful for diagnosing colorectal cancer. But it is necessary to remember that isoenzymes of ADH and ALDH are present in large quantities in the liver, and also occur in the different organs such as gastrointestinal tract, lungs, kidneys and breast [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic studies revealed that women have lower levels of gastric and hepatic ADH, resulting in increased blood alcohol levels and EtOH toxicity (Frezza et al, 1990;Chrostek et al, 2003). However, Maly and Sasse (1991) found that hepatic ADH activity is enhanced in women.…”
Section: Introductionmentioning
confidence: 99%
“…However, Maly and Sasse (1991) found that hepatic ADH activity is enhanced in women. Although only minor variations in ALDH activity between men and women have been reported, ALDH activity is higher in male hamsters than in females (Maly and Sasse, 1991;Lee et al, 2001;Chrostek et al, 2003).…”
Section: Introductionmentioning
confidence: 99%